Root canal morphology of primary molars by clearing technique: An in vitro study - Farhin Katge (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2018)
Objective: The objective of the study was to study root canal morphology of primary molars by clearing technique and to observe for any variations. Materials and Methods: One hundred and twenty extracted primary molars were divided into four groups (n = 30); Group I = maxillary first, Group II = maxillary second, Group III = mandibular first, and Group IV = mandibular second. The samples were subjected to decalcification, clearing, and dye penetration. The data regarding the root canal morphology of each sample were tabulated based on the number of root canals, curvature of the root canal, and root canal configuration. Descriptive statistics were applied. Results: According to Vertucci's root canal configuration in Group I, mesiobuccal root exhibited 93.10% Type I, 6.90% Type II, and 6.90% Type IV; distobuccal root had 95.65% Type I and 4.35% Type IV; and palatal roots had 100% Type I canal configuration. In Group II, mesiobuccal root showed 90% Type I and 10% Type IV; distobuccal root had 100% Type I; palatal root exhibited 96.30% Type I and 3.70% Type III. In Group III, mesial root showed 20% Type I, 6.67% Type III, and 73.33% Type IV and distal root had 76.67% Type I and 23.33% Type IV. In Group IV, mesial root exhibited 100% Type IV and distal root had 43.33% Type I and 65.67% Type IV canal anatomy. Conclusion: Vertucci's Type I root canal configurations were most frequently observed.